Peranan Kepolisian Resor Tebing Tinggi Dalam Penegakan Hukum Terhadap Tindak Pidana Ujaran Kebencian Di Media Sosial - Renal Eldinata Samosir; Taufik Siregar; Rizkan Zulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The presence of such sophisticated information technology has given a new nuance by touching almost all aspects of life. Technology has made it easy for people to carry out daily activities to meet their needs, as well as facilitate interaction between human beings wherever they are. This research is a normative juridical research that uses a literature study and field study approach. The data collection tool used in this study used the interview method. Interviews were conducted on informants or investigators at the Tebing Tinggi Resort Police. Data analysis was carried out qualitatively. The results of the study indicate that the role of the police in law enforcement against hate speech crimes on social media as regulated in Law no. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions (UU ITE) and Law no. 2 of 2002 concerning the Indonesian National Police. The role of the police includes receiving reports or complaints about the occurrence of an event that is reasonably suspected of being a criminal act; it is obliged to immediately carry out the necessary investigative actions; As an investigator who knows, receives a report or complaint about the occurrence of an event that is reasonably suspected to be a criminal act, he is obliged to immediately carry out the necessary investigative actions and find and collect evidence so that the case becomes clear so that the suspect can be found.